Movie madness - Keene, Carolyn (Keene, Carolyn. Nancy Drew clue book, 2016)
School is out for summer and the timing is great because a movie is filming in River Heights, and Nancy, Bess, and Georgeu2014along with a bunch of their classmatesu2014get to be extras in a scene shot at the playground! Help Nancy and her friends find a prop thatu2019s gone missing from the superhero movie set in this interactive Nancy Drew chapter book mystery series.